.NET Test Automation Recipes A Problem-Solution Approach - McCaffrey, James (Apress : Imprint: Apress, 2006)
If you develop, test, or manage .NET software, you will find .NET Test Automation Recipes: A Problem-Solution Approach very useful. The book presents practical techniques for writing lightweight software test automation in a .NET environment and covers API testing thoroughly. It also discusses lightweight, custom Windows application user interface automation and teaches you low-level web application user interface automation. Additional material covers SQL stored procedure testing techniques. The examples in this book have been successfully used in seminars and teaching environments where they have proven highly effective for students who are learning intermediate-level .NET programming. You'll come away from the book knowing how to write production-quality combination and permutation methods.